2020
DOI: 10.21203/rs.3.rs-19614/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Torque Mechanical Evaluation for 3D Printed Orthodontic Springs with Different Parameters: Invitro Study

Abstract: Background: The purpose of the presented investigation is to evaluate the resulting torque on loaded 3D printed springs using different coil thickness and length. Methods: Specimens were designed and printed using the 3D printer MAX (Asiga, Sydney, Australia) with 3D printable, experimental, flexible material (Code:BM2008, GC, Tokyo, Japan). The specimens were divided into three groups according to spring coil design. Control group (n=18), length group (n=19) and thickness group (n=22). Groups were tested usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The control group with 4 coils was selected referring to a study conducted by Othman et al who found that comparing between the conventional laboratory fabricated springs with the CAD/CAM methods had a significant difference for material as well as design comparing compression to force ratio. The design with 4 coil numbers and variable wire thickness directly affects the mechanical properties for printable orthodontic resins and exhibit that CAD/CAM orthodontic springs can be printed and mechanically tested in order to bring out a new treatment possibility in orthodontics using the 4 coils springs design [15].…”
Section: Methodsmentioning
confidence: 99%
“…The control group with 4 coils was selected referring to a study conducted by Othman et al who found that comparing between the conventional laboratory fabricated springs with the CAD/CAM methods had a significant difference for material as well as design comparing compression to force ratio. The design with 4 coil numbers and variable wire thickness directly affects the mechanical properties for printable orthodontic resins and exhibit that CAD/CAM orthodontic springs can be printed and mechanically tested in order to bring out a new treatment possibility in orthodontics using the 4 coils springs design [15].…”
Section: Methodsmentioning
confidence: 99%